Concordance between trucut needle biopsy and surgical specimen for estrogen receptor, progesterone receptor and human epidermal growth factor receptor status in breast cancer - Sakalle, Shishir; Tandon, Puneet; Balani, Sharda; Malik, Reeni; Pal, Sudhir; Choudhary, Rajni; Sulya, Manish; Jain, Pramila (International Journal of Research in Medical Sciences, 2025)
Background: Breast cancer is the most common malignancy among women worldwide, contributing significantly to cancer-related morbidity and mortality. Estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor (HER2/neu) status are crucial for prognosis and treatment planning. Trucut needle biopsy is widely used for preoperative biomarker assessment; however, discrepancies with surgical specimen results may affect clinical decisions. Methods: A cross-sectional study was conducted at Gandhi Medical College and Hamidia Hospital, Bhopal, from August 2022 to January 2024, including 32 cases of invasive ductal carcinoma. Immunohistochemistry was performed on trucut biopsies and surgical specimens to assess ER, PR, and HER2/neu expression. Concordance rates, sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated. Statistical analysis used SPSS, with p<0.05 considered significant. Factors influencing discordance, including tumor heterogeneity, fixation techniques, and preanalytical variables, were evaluated. Results: ER showed high concordance (90.6%), sensitivity (83.3%), specificity (100%), PPV (100%), and NPV (82.4%). PR demonstrated moderate concordance (78.1%), sensitivity (73.3%), specificity (82.4%), PPV (78.6%), and NPV (77.8%). HER2/neu showed moderate to low concordance (51.6%), sensitivity (64.7%), specificity (86.7%), PPV (84.6%), and NPV (68.4%). HER2/neu discordance was linked to intratumoral heterogeneity, staining variability, equivocal results requiring fluorescence in situ hybridization. Conclusions: Trucut biopsy is highly reliable for ER and PR assessment but shows moderate reliability for HER2/neu, warranting confirmatory testing in borderline cases. Awareness of potential discrepancies and supplementary diagnostics can enhance preoperative accuracy and guide personalized breast cancer management.